Comparison of tracheoscopy and portable chest X-Ray in the evaluation of infant tracheostomy tube position. (February 2021) - Keane, Allison; Saadi, Robert A.; Slonimsky, Einat; Wilson, Meghan; May, Jason
Abstract: Objective: To compare tracheoscopy and chest radiograph measurements of tracheostomy tube position in infants. Study design: Retrospective chart review. Setting: Otolaryngology Department at Penn State Milton S. Hershey Medical Center. Subjects and methods: All cases of pediatric patients who underwent tracheotomy at less than 1 year of age from 2014 to 2019 were reviewed. Patients were included if they had both intraoperative measurement of tracheostomy tube position relative to the carina by tracheoscopy and postoperative chest radiograph. Documented intraoperative findings were compared to measurements made on chest radiograph by an attending radiologist blinded to the intraoperative measurements. Results: The study included 66 patients; 30 patients (14:16, M:F) had available data. The mean distance from the distal tracheostomy tube to the carina measured by tracheoscopy was 8.88 mm (range, 3.5–20 mm) and measured radiographically was 11.71 mm (range, 2.4–23.3 mm). The mean difference between the measurements was 2.82 mm (p-value = 0.016). Ninety percent (n = 27) of patients had measurements that differed by greater than 2 mm; 53% (n = 16) had measurements that differed by 5 mm and 1% (n = 3) had measurements differing by greater than 10 mm. Conclusion: In the infant population, significant discrepancy was found between direct tracheoscopy and chest radiograph measurements of the tracheostomy tube position. Measurements obtained by chest radiographs tend to overestimate the relative distance of the distal tracheostomy tube to the carina as compared to that of tracheoscopy. Clinical decisions regarding changes to tracheostomy tube sizes should mostly rely on tracheoscopy performed with the patient supine. Highlights: Portable chest X-ray and tracheoscopy measurements of tracheostomy tubes do not correlate. Tracheostomy tube distance from carina should be measured by direct tracheoscopy. Clinical decision-making regarding trach tube size should not be based solely on bedside X-ray.